Discussion on the Teaching of "Engineering Materials" with Philosophy Thoughts. Issue 1 (March 2021) - Liu, Yan; Qu, Yanpeng; Song, Qinghua; Chen, Songying
Abstract: The college students in engineering can improve their professional level and comprehensive ability through learning the knowledge with philosophical ideas. In the teaching practice on the course of engineering materials, the authors constructed the contents including the ideological and political factors, and linked the philosophy thoughts with the professional education. The main results are as follows. We understand the similarities of engineering materials and life connotation, and clarify the internal relation and interaction mechanism between materials and objective environment through explaining the environmental theory; We know that we should find out the the principal contradiction during the engineering materials selection and life path selection through the contradiction theory; We understand the influence of various factors on the change of material performances and the influence of creative tools on the development of disciplines through the things correlation theory;We recognize that we need to sum up the historical experiences and learn the failure analysis methods to reduce the probability of disaster accidents through the philosophy methodology. Some relevant teaching cases are introduced in this paper.